2017
DOI: 10.3103/s1067821217040149
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of mechanical properties of products manufactured using selective laser melting of powdered materials

Abstract: Санкт-Петербургский политехнический университет Петра Великого ОАО «Климов», г. Санкт-Петербург Статья поступила в редакцию 01.02.16 г., доработана 29.02.16 г., подписана в печать 02.03.16 г. Рассмотрены причины возникновения анизотропии свойств в изделиях, изготавливаемых по технологии селективного лазерного плавления металлических порошковых материалов. Представлены результаты оценки механических свойств образцов из сплавов основе титана Ti-6Al-4V, ВТ6 и жаропрочного никелевого сплава Inconel 718 в различных… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Microstructural and mechanical anisotropy of additively manufactured metals, particularly titanium, is well understood [76][77][78][79][80]. The results of this study showed that there is also a significant amount of dimensional anisotropy.…”
Section: Additive Manufacturingmentioning
confidence: 64%
“…Microstructural and mechanical anisotropy of additively manufactured metals, particularly titanium, is well understood [76][77][78][79][80]. The results of this study showed that there is also a significant amount of dimensional anisotropy.…”
Section: Additive Manufacturingmentioning
confidence: 64%
“…In the SLM-produced parts, in addition to the speci c structure, defects may be present -mainly voids and lack of fusion [54]. Although no voids and microcracks were detected on the sample surface by optical microscopy, in [8,26] it is reported that porosity is actually very common in SLM-produced parts.…”
Section: Initial Microstructure Of Slm-produced and Wrought Ti-6al-4vmentioning
confidence: 99%
“…From the manufacturing perspective, AM processes tend to be at least as restrictive, if not more, in terms of manufacturability constraints than traditional processes. [29,[48][49][50] The layer-based nature of all AM processes produce anisotropic material properties in the final parts [17,[51][52][53] , the surface finish of final parts can be poor [17,[54][55][56] , and the inherent residual stresses from some processes can dramatically reduce the fatigue life of the parts [57][58][59] . Due to these and other considerations, AM-made parts can be prone to fracture and may have poor dimensional accuracy for some processes and materials.…”
Section: Introductionmentioning
confidence: 99%